Adoption of Blockchain and Cloud Computing in Morocco Insurance Sector: A SLR Approach - Saeed, Maryam; Arshed, Noman (International Journal of Islamic Economics and Governance, 2025)
This paper aims to investigate the challenges and prospects regarding adoption of Blockchain and Cloud Computing in the Moroccan Insurance Industry, in an Islamic country context, through a Systematic Literature Review (SLR). Several millennia prior to Christ, the concept of insurance was discovered (BC). Shifting or distributing risks was a tactic used by traders from Babylonia and China in the second and third millennia BC. Insurance is now the backbone of the economy, but increasing its ubiquity in developing countries is challenging. The recent emergence of IoT, Big Data, and InsurTech prompted the fourth insurance business revolution in the industrialized world. This study looks at the issues with Blockchain and Cloud Computing adoption and possible solutions to increase insurance coverage in Morocco. A PRISMA approach opt to find pertinent literature from Google Scholar or Emerald, by using number of keywords. The selected studies were evaluated against predefined inclusion and exclusion criteria. This analysis identified multiple barriers that hinder the adoption of Blockchain and Cloud Computing in Morocco’s insurance industry, and it also highlighted potential mitigation strategies. The findings offer actionable insights that could assist policymakers in improving service delivery across the sector. Morocco’s insurance sector faces Blockchain and Cloud adoption challenges, including security risks, infrastructure limitations, skill shortages, and regulatory gaps. Solutions focus on government support, collaboration, staff training, and secure, compliant technological implementation.